Pelatihan Pembutan Brosur Dengan Adobe Photoshop Pada SMA PGRI Pagar Alam - Siti Muntari; Elpita Aisah; Fitria Rahmadaynti (Pusat Riset dan Inovasi Nasional, 2023)
An indicator of a good village is having a clean environment and local residents free from all diseases. In addition, local residents have commodities to be more independent in terms of economic development. This is of course not only the responsibility of village officials, but requires the support and cooperation of local residents as well. Therefore it is necessary to make use of the village environment which can realize the indicators previously mentioned. The first step that can be taken is to start with your own yard. Because based on observations, the service team found that in the partner village, namely Balombong village, it had not been used properly and there were empty lands in the residents' yards. So that the purpose of implementing this service is to provide education for residents to be able to take advantage of the yard by planting fruit in pots. This can make the environment more beautiful, healthy and the results can help the local economy